Conduction paths of backbones for thermal enhancement of nanocomposite phase change materials. (25th November 2019) - Zhou, Tao; Du, Yanping; Zhao, Changying; Wang, Yongzhen; Zhao, Jun
Summary: Thermal energy storage (TES) based on phase change materials (PCMs) has become a research hot spot due to its high energy storage density and maintained operating temperature during the phase change. However, as PCM has a poor thermal conductivity that can be as low as 0.2~0.5 W/m·K, the charging/discharging processes of PCM modules are significantly restrained, which severely affects the application of the TES technology in industrial sectors. This study concerns the improvement of the effective thermal conductivity of composite PCM formed by adding nanoparticles with high thermal conductivity into different PCMs. A theoretical model is established to reveal the intrinsic mechanism for the promotion of thermal conductivity of composite PCM consisting of nanoparticles. The results show that aggregation and interfacial thermal resistance are the main reasons for the change of the thermal conductivity. By forming effective conduction paths composed of backbones in the composite PCM, the average thermal conductivity can be improved significantly, which can be as high as 10~50 W/m·K with a wide range of volume fraction of the additives. Abstract : A theoretical model is established to reveal the intrinsic mechanism for the promotion of thermal conductivity of composite PCM consisting of nanoparticles. Results in this study show that aggregation and interfacial thermal resistance are the main reasons for the change of the thermal conductivity. By forming effective conduction paths composed of backbones in the composite PCM, the average thermal conductivity can be improved significantly, which can be as high as 10~50 W/mK with a wide range of volume fraction of the additives.